Gender and Politics The State of the Discipline - Bayes, Jane (Verlag Barbara Budrich, 2012)
This timely collection offers a fresh look on the impact of gender perspectives in the discipline of political science at the beginning of the 21st century. Jane Bayes combats the Eurocentric focus that has characterised both fields and suggests viable alternatives for the future of the disciplines.